2015
DOI: 10.1093/mnras/stv2436
|View full text |Cite
|
Sign up to set email alerts
|

Beating non-linearities: improving the baryon acoustic oscillations with the linear point

Abstract: We propose a new way of looking at the Baryon Acoustic Oscillations in the Large Scale Structure clustering correlation function. We identify a scale s LP that has two fundamental features: its position is insensitive to non-linear gravity, redshift space distortions, and scale-dependent bias at the 0.5% level; it is geometrical, i.e. independent of the power spectrum of the primordial density fluctuation parameters. These two properties together make s LP , called the "linear point", an excellent cosmological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(96 citation statements)
references
References 34 publications
6
90
0
Order By: Relevance
“…1 for ω b , ωc and ns. As expected [14], non-linear physics reduces sLP at z=0 to ∼ 99% of its high-z value for the fiducial cosmology, motivating a 0.5% correction to keep s non−lin LP within 0.5% of s lin LP over the full range of redshift values.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…1 for ω b , ωc and ns. As expected [14], non-linear physics reduces sLP at z=0 to ∼ 99% of its high-z value for the fiducial cosmology, motivating a 0.5% correction to keep s non−lin LP within 0.5% of s lin LP over the full range of redshift values.…”
Section: Resultssupporting
confidence: 65%
“…3, we display the rulers' dependence for 0.5 < n s < 2. The n s dependence of the LP is still within the 0.5% LP intrinsic uncertainty [14], and can thus be neglected in the cosmological analysis. For n s > 2, this no longer the case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [19], the authors have shown that the Linear Point standard ruler (LP) provides a PG-BAO method, as it precisely shares all the (A) requirements. It is defined as the mid-point between the BAO peak and the dip of the 2-point correlation function.…”
Section: Introductionmentioning
confidence: 99%